ANALISIS BUTIR SOAL PILIHAN GANDA MATERI NILAI-NILAI KRISTIANI MENJADI PEGANGAN HIDUPKU UNTUK KELAS VII SMP NEGERI 1 NABIRE - Marzel Joska Hitipeuw; Alfrida Balisa; Yonece Delila Mara; Wawan Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning evaluation plays a strategic role in measuring the achievement of educational objectives and serves as a basis for improving the learning process. In the context of Christian Religious Education, evaluation focuses not only on cognitive aspects but also on the internalization of Christian values ​​as a guide to life, thus requiring high-quality and tested instruments. This study aims to analyze the quality of multiple-choice questions on the topic